PHILOSOPHY AND MADZHAB OF DEVELOPMENT ISLAMIC EDUCATION CURRICULUM - Prasetya, Aziz; Fitri, Agus Zaenul; Aziz, Abdul (PROGRES PENDIDIKAN, 2024)
Studying the philosophy of education means that we are invited to think deeply (radically), systematically, universally/openly as an effort to position ourselves in seeking the truth, the core of the problem, the essence, and the steps in how we reflect ourselves in a reflection on the realities of the world based on education. So, this reflection consciously focuses on the world of education, in the development of which we are invited to innovate and also develop Renaissance education, especially in Islamic education. Researchers examine the object of study in terms of educational philosophy and also the Madzhab of educational development, which objectively focuses on curriculum development. The method used in this research is the library research method, namely data and literature obtained from the results of reviewing existing libraries and literature. Researchers show that the development of an Islamic education-based curriculum is part of the development and innovation of what is explained theoretically in the School of Educational Development (Progressivism School, Essentialism School, Perennialism School, Reconstructionism School, and also Existentialism School), so that the implementation of education and development The education that is studied in this research shows that there is progress in the flexible perspective of educational development.